Effect of MgSO4 Solution on the Physicochemical and Mechanical Properties of OPC-Metakaolin and OPC-Metakaolin-Limestone Blends (Journal of Material Science and Technology Research, 2021)
This study aims to investigate the effect of MgSO4 solution on the durability of the pastes made of ordinary Portland cement (OPC) blended with 10, 20 and 30 wt.% metakaolin (MK) and the pastes made by partial substitution of metakaolin in the mix containing 30% metakaolin by 5 and 10 wt.% limestone (LS). All pastes were prepared using the suitable amount of water for standard consistency. The pastes cured in tab water for 28 days then divided into two sets; the first one continued for hydration in tab water up to two years. The second set was immersed in 5% MgSO4 solution for the same period of hydration. Compressive strength, chemically combined water content and free lime content of the two sets of the hardened cement pastes were determined and compared to each other. Also, mass change of the set samples immersed in sulphate solution was investigated. In addition, phase composition and microstructure of some selected samples in the two solutions were examined by using XRD and SEM techniques respectively. It was found that the paste made of (70% OPC + 20% MK + 10% LS) represent the most durable against sulphate attack.